Issid planthoppers from Bach Ma and Phong Dien in Central Vietnam: (II) Tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae) - Jérôme Constant; Hong Thai Pham (European Journal of Taxonomy)
Eight species of Issidae (Hemiptera: Fulgoromorpha) belonging to the tribe Hemisphaeriini, including seven species new to science, were collected in recent years in Bach Ma National Park and Phong Dien District in Thừa Thiên-Huế Province in Central Vietnam. One belongs to a new genus, Varisphaerius gen. nov., erected for the new species V. hoaiae sp. nov. from Bach Ma National Park. A new species of the genus Ceratogergithus Gnezdilov, 2018, C. pictus sp. nov., is described from Bach Ma National Park and Phong Dien District and represents the first record of the genus in Vietnam. Two new species of the genus Hemisphaerius Schaum, 1850 are described: H. annamiticus sp. nov. and H. thaydoius sp. nov. from several localities in the Central Annamites; one new species of the genus Gergithoides Schumacher, 1915: G. devyveri sp. nov. from Bach Ma National Park; two new species of the genus Ishiharanus Hori, 1969: I. dinhanus sp. nov. from the summit of Bach Ma National Park and I. pulchellus sp. nov. from Bach Ma National Park, Phong Dien District and several localities in the Central Annamites. The distribution of I. iguchii (Matsumura, 1916) is expanded southwards by about 500 km, to Central Vietnam, in Bach Ma and Vu Quang National Parks. The species is also recorded from the capital Hanoi and the four provinces of Ha Tinh, Hai Phong, Thanh Hoa and Thừa Thiên-Huế for the first time. These eight species, added to the eight species of the tribe Parahiraciini previously recorded/described from Thừa Thiên Huế Province, amount to a total number of 16 species of Issidae for this province. Accordingly, the Vietnamese issid fauna now counts 65 species in 34 genera. Additionally, the first observation of a trophobiotic interaction of a member of the tribe Hemisphaeriini is reported between Ceratogergithus pictus sp. nov. and ants of an unidentified species of the genus Camponotus Mayr, 1861 (Hymenoptera: Formicidae: Formicinae).